2021
DOI: 10.5194/jm-40-61-2021
|View full text |Cite
|
Sign up to set email alerts
|

Biogeographic distribution of three phylotypes (T1, T2 and T6) of <i>Ammonia</i> (foraminifera, Rhizaria) around Great Britain: new insights from combined molecular and morphological recognition

Abstract: Abstract. Ammonia is one of the most widespread foraminiferal genera worldwide. Three phylotypes (Ammonia sp. T1, T2 and T6), commonly encountered in the northeast Atlantic, are usually associated with the morphospecies Ammonia tepida. The biogeographic distribution of these three types was previously investigated in coastal environments around Great Britain based on genetic assignations. A new method was recently developed to recognize these three phylotypes based on morphological criteria (i.e. pore size and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Ranges of morphometric characteristics useful for species determination were provided (Hayward et al, 2004). Other biometric approaches assessed the same characteristics and demonstrated that only the pore diameter and the suture elevation in the central part of the spiral side may facilitate a secure species differentiation, in particular among three morphologically similar genotypes (Richirt et al, 2019(Richirt et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Ranges of morphometric characteristics useful for species determination were provided (Hayward et al, 2004). Other biometric approaches assessed the same characteristics and demonstrated that only the pore diameter and the suture elevation in the central part of the spiral side may facilitate a secure species differentiation, in particular among three morphologically similar genotypes (Richirt et al, 2019(Richirt et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…For example, shared genotypes (e.g., Type IIa Hastigerina and Type IIIb Globigerinella) are present in the Indian and Southern Atlantic oceans (reviewed in Weiner et al, 2012Weiner et al, , 2014. There are also a few studies that estimate gene flow for benthic species (Hayward et al, 2004(Hayward et al, , 2021Richirt et al, 2021), although more work is needed here. Below we discuss the communities observed in each of these habitats.…”
Section: Habitat-specific Foraminifera Communitiesmentioning
confidence: 99%
“…Despite the progress in characterizing foraminifera biodiversity, the presence of cryptic diversity and different genotypes in different localities are the subject of recent debate, with the suggestion that foraminifera may show patchy distribution across a broader spatial scale (Gooday & Jorissen, 2012; Richirt et al, 2021). One reason for this is that previous molecular studies only focused on foraminiferal diversity in specific environments (Cordier et al, 2019; Lecroq et al, 2011; Shi et al, 2020).…”
mentioning
confidence: 99%
“…To ensure an objective assessment of the stereomicroscope and the SEM methods, independent identifications were made by two different investigators. First, specimens were identified with a stereomicroscope using the two criteria proposed by Richirt et al [5,12]. For the first criterium, the elevation of the sutures on the spiral side, i.e., either flush…”
Section: Ammonia Phylotype Identificationmentioning
confidence: 99%
“…Despite the considerable efforts made by taxonomists to link morphology-based (e.g., morphospecies) and molecular-based (e.g., phylotypes) taxonomy [3][4][5], the complexity of the taxonomy of Ammonia has not yet been totally disentangled and the genus still suffers from taxonomical uncertainties [2,4]. One of the most exhaustive recent publications recognizes 67 Ammonia and related taxa that can be morphologically discriminated, with possibly 30 or more additional living species uniquely distinguishable by molecular sequencing [2].…”
Section: Introductionmentioning
confidence: 99%